2022
DOI: 10.1021/acs.jpcc.2c04497
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer in Conjugated Polymer Electrolyte Complexes: Impact of Donor–Acceptor Interactions on Microstructure, Charge Separation, and Charge Recombination

Abstract: Conjugated polyelectrolyte complexes (CPECs) are an artificial light-harvesting platform formed by pairing oppositely charged conjugated polyelectrolytes in solution. We demonstrate that selective pairing of poly[3-(potassium-4-alkanoate)thiophene-2,5-diyl] (PTAK) of various regioregularity and side-chain lengths with either methyl viologen or an electrolytic naphthalene diimide electron acceptor supports different PTAK microstructures based on specific donor−acceptor stacking relationships. Alteration in micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(39 citation statements)
references
References 79 publications
2
37
0
Order By: Relevance
“…In separate work, we examined ultrafast charge generation in CPECs of PTAK with small-molecule electrolytes, including methyl viologen (MV 2+ ) and an electrolytic naphthalene diimide (ENDI). A bathochromic red shift of the PTAK absorption band is observed in small-molecule/polymer complexes, indicating that these pairings afford significant changes in polymer confirmation as well as intermolecular orbital mixing. , Hence, orbital mixing between polymer donors and small-molecule acceptors yields ultrafast charge generation upon excitation of PTAK in these CPECs . Notably, we see an increased efficiency for ultrafast polaron formation in these complexes with increased excitation energy, which we attribute to greater coupling of the local PTAK exciton with the CT excitons at higher energies. ,, Further, we infer from polaron signatures that are formed on sub-ps timescales that the primary photophysical dynamic in the small-molecule/polymer systems is direct charge separation rather than exciton migration, despite the potential for significant exciton delocalization.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…In separate work, we examined ultrafast charge generation in CPECs of PTAK with small-molecule electrolytes, including methyl viologen (MV 2+ ) and an electrolytic naphthalene diimide (ENDI). A bathochromic red shift of the PTAK absorption band is observed in small-molecule/polymer complexes, indicating that these pairings afford significant changes in polymer confirmation as well as intermolecular orbital mixing. , Hence, orbital mixing between polymer donors and small-molecule acceptors yields ultrafast charge generation upon excitation of PTAK in these CPECs . Notably, we see an increased efficiency for ultrafast polaron formation in these complexes with increased excitation energy, which we attribute to greater coupling of the local PTAK exciton with the CT excitons at higher energies. ,, Further, we infer from polaron signatures that are formed on sub-ps timescales that the primary photophysical dynamic in the small-molecule/polymer systems is direct charge separation rather than exciton migration, despite the potential for significant exciton delocalization.…”
Section: Introductionmentioning
confidence: 58%
“…We focus specifically on the photoinduced dynamics of CPECs composed of the energy donor–acceptor pair poly­([fluorene]-alt-co-[phenylene]) (PFPI) and poly­[3-(potassium-4-alkanoate)­thiophene-2,5-diyl] (PTAK), presented in Chart , to provide further insight into charge generation in combination with energy transfer. The shapes and energies of absorption and emission spectra of PTAK in CPECs are determined by the prevalent excitonic coupling between thiophene monomers, providing a window into polymer microstructure. Hence, CPECs containing PTAK have been valuable for discerning how the character, rates, and efficiencies of photophysical processes depend on polymer microstructure. , Prior work has determined that PFPI:PTAK CPECs form structurally ordered complexes at a 60:40 charge ratio that exhibit extended (ordered) regions of polymer chains and decreased PTAK π-stacking. , We observed that PFPI-to-PTAK Förster Resonant Energy Transfer (FRET) occurs on a timescale of ∼200 fs (or faster) in these complexes . We found that excited PTAK (singlet) persists on longer timescales in complexes at this charge ratio compared to free PTAK.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the activity appears to be more dependent on the density of trap states rather than on its distribution which points to trap lling playing an important role in the generation of active and mobile charges. 76,77 Next, we focus on the impact of particle size and surface area on photoactivity. Typically, semiconductor materials with smaller particle sizes tend to have large surface area, indicating potential reaction sites and demonstrate high light absorption properties which may favour efficient photoactivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the activity appears to be more dependent on the density of trap states rather than on its distribution which points to trap filling playing an important role in the generation of active and mobile charges. 76,77…”
Section: Discussionmentioning
confidence: 99%